Abundance and Diversity of Dimethylsulfoniopropionate Degradation Genes of Roseobacter Group in the Northern South China Sea - Sun, Fulin; Wang, Youshao; Jiang, Zhaoyu; Sun, Cuici; Wang, Yutu; Wu, Meilin (Frontiers in Marine Science, 2022)
Bacterial degradation of dimethylsulfoniopropionate (DMSP) plays a significant role in ecosystem productivity and global climate. In this study, the abundance and diversity of Roseobacter group DMSP degradation genes were explored in spatial scale of the South China Sea (SCS). Quantitative PCR showed that a higher abundance of dmdA (DMSP demethylase) and dddP (DMSP lyase) genes was detected above 75 m than deep water, especially in surface water. A high ratio of dmdA/dddP existed in all sites and increased with water depth, indicating that demethylation was the main degradation pathway in the Roseobacter group. High-throughput sequencing analysis showed that distribution of dmdA gene had a significant layering structure in the northern SCS, and high taxonomic diversity of dmdA gene was observed in near-surface waters (25 and 50 m). DmdA gene in the Roseobacter group, such as Leisingera, Nioella, Roseobacter, Roseovarius, Donghicola, Phaeobacter, and Tateyamaria, had remarkable specificity due to the effect of different sites and water depths. Different ecological strategies of DMSP degradation may be used by members of the bacterial community harboring demethylation genes. In addition, many dmdA sequences were affiliated with unidentified bacteria, indicating that the SCS reserved high diversity of DMSP-degrading bacteria. Canonical correspondence analysis (CCA) suggested that temperature and depth were the most important factors to determine the taxonomic distribution of DMSP degradation genes in the Roseobacter group, as well as their abundance. This study highlighted the understanding of the role of Roseobacter group in DMSP degradation in the tropical ocean.